The Effect of Kaizen Culture, Motivation and Work Discipline on Employee Performance at PT Mattel Indonesia East Plant - Kosim, Abdul; Gunawan, Ahmad (Jurnal Manajemen, 2024)
Human resource management seeks to take a strategic role in realizing the company’s vision and mission through the formation of a culture that fosters optimal performance of its human resources. This relates to the function of corporate culture as a priority setting mechanism or the way things are done around here, establishing operational norms, instilling shared dedication, and guiding attitudes and behaviors, including work motivation. This study aims to determine the effect of Kaizen Culture, Motivation and Work discipline on employee performance at PT Mattel Indonesia East Plant. This study uses quantitative techniques, the results of respondents’ questionnaires, and an approach that emphasizes the objective measurement of social phenomena. The population was 300 people and the sample was 75 respondents. The data collected was then analyzed using the analysis method with the help of SPSS25 software. Based on the results of research on Kaizen Culture variables, Motivation and Work Discipline on Employee Performance have a positive influence. Which is indicated by the results of Fhitung 120.881, it can be seen that Fhitung (120.881)> Ftabel (0.117) and the significance value (0.000) < (0.05) This means that there is a positive and significant influence between the variables of Kaizen Culture, Motivation, and Work Discipline on Employee Performance. The main research results show that all hypotheses have a significant positive relationship. The results obtained from this research are expected to provide benefits for Company management in analyzing kaizen culture, motivation and work discipline on employee performance.